A Focus on Domestic Structures: Best Interests of the Child in the Concluding Observations of the UN Committee on the Rights of the Child. Issue 2 (2nd April 2020) - Sormunen, Milka
ABSTRACT: The views of human rights treaty bodies are essential in understanding key treaty provisions. However, the interpretations of the Committee on the Rights of the Child, the monitoring body of the United Nations Convention on the Rights of the Child, are mostly scattered in concluding observations that the Committee issues in response to states' periodic reports. Through systematic analysis, this article shows how the Committee conceptualises the best interests of the child, an important yet indeterminate concept for the children's rights framework and human rights law in general, in the concluding observations. The article argues that the Committee connects best interests to various recurring contexts. Most importantly, the Committee focuses on active measures through which states are supposed to implement the best interests of the child. These six cross-cutting themes—legislative measures, integration in practices, cooperation, awareness-raising and training, resources, and monitoring—correspond to the general measures of implementation that the Committee has previously identified, and they are used as a framework to analyse the concluding observations. The results demonstrate the importance of domestic structures in implementing human rights. They can also be interpreted as reflecting the Committee's understanding of best interests as a positive obligation.